THE CONCENTRATION EFFECT OF K2SO4 ELECTROLITE SOLUTION ON GLOW DISCHARGE PLASMA ELECTROLYSIS - Harianingsih, Harianingsih; Kusumaningrum, Maharani; Bunyamin, Bunyamin (Universitas Wahid Hasyim, 2022)
Plasma electrolysis is currently an environmentally friendly technology that is used as an alternative to nitrogen fixation, clean water treatment, batik waste degradation and the synthesis of other compounds. The success indicator of plasma electrolysis technology is seen from the formation of glow discharge. One of the factors that influence the formation of plasma in this method is the electrolyte solution. The electrolyte solution used in this study is K2SO4 because its conductivity causes electron jumps. This study aims to determine the effect of various concentrations of K2SO4 electrolyte solution on glow discharge plasma at the anode.In the plasma electrolysis reactor with stainless steel cathode and tungsten anode and 0.01 M electrolyte solution; 0.02 M; and 0.03 M K2SO4. The formation of glow discharge plasma occurs at the anode. Changes in concentration affect the critical voltage (VD) where the higher the concentration (0.03 M), glow discharge occurs at a lower voltage (600 V). This is due to the presence of high dielectric strength in the solution causing lower discharge strength to occur in solutions with lower electrolyte concentrations.Keywords: anode, plasma electrolysis, K2SO4 electrolyte, glow dischargeÂ